Study of menstrual pattern changes in patients accepting injection depo-medroxyprogesterone acetate versus levonorgestrel intrauterine system - Jain, Saloni; Mani, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Changes in menstrual bleeding patterns are a major cause of hormonal contraceptive discontinuation. DMPA and LNG IUS both are hormonal contraceptives and are used by most of the women worldwide for various gynaecological conditions. The aim of the present study was to compare menstrual pattern changes in patients accepting injection DMPA and LNG-IUS for various gynaecological indications. Methods: This randomized controlled trial was conducted among 70 women aged 18 years or older with heavy menstrual bleeding in the department of Obstetrics and Gynaecology, Chhatrapati Shivaji Subharti Medical College, Meerut. The study comprised of two groups having 35 patients each i.e. Group 1 (patient who opted for LNG IUS) and Group 2 (patient who opted injection DMPA). The menstrual pattern changes were assessed at 1month, 3month and 6th month interval. Patient were asked to maintain a menstrual calendar wherein she would keep a record of the no. of days along with dates when she has spotting per vaginum/bleeding per vaginum and the amount of blood loss explained to her through the pictorial blood assessment chart. Results: Reduction in median menstrual blood loss was significantly greater in the LNG IUS group (-128.12mL, range -393.6 to 328.5 mL) than in the DMPA group arm -17.8 mL, range -271.5 to+78.6 mL, p<0.001). Conclusions: LNG IUS reduces menstrual blood loss more effectively than DMPA.